Utilization of Digital Technology and Entrepreneurial Interest in Efforts to Alleviate Poverty and Food Independence in the Flamboyan Women Farmers Group Bogor City: Pemanfaatan Teknologi Digital Dan Minat Kewirausahaan Dalam Upaya Pengentasan Kemiskinan Dan Kemandirian Pangan Pada Kelompok Wanita Tani Flamboyan Kota Bogor - Ani Mekaniwati; Wahyu Indra Satria; Tarida Marlen; Dika M. Ridwan; Adelia Putri Belinda; Hosea Rianto (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2024)
The Women Farmers Group (KWT) is a community that focuses on carrying out activities related to agriculture where the group members consist of women. This community group is targeted to become activity partners. The focus of this service activity is on social humanities aspects, with an emphasis on the economic side and human resources of MSMEs, in order to eradicate poverty and food independence. Service activities will be carried out through 3 (three) stages, namely preparation, implementation, and post-activity monitoring and evaluation. Carrying out service activities not only provides assistance in the form of physical goods and buildings but also hydroponic training to support partners' readiness in carrying out their business. With KWT Flamboyan as a service partner, it is hoped that the women farming community will be able to run a sustainable hydroponic plant cultivation business with greater profits in the future.